Experimental observation of shaking soliton molecules in a dispersion-managed fiber laser - Xia, Ran (2022)
Recent progress in real-time spectral interferometry enables access to the internal dynamics of optical multisoliton complexes. Here, we report on the first, to the best of our knowledge, experimental observation of shaking soliton molecules by means of the dispersive Fourier transform technique. Beyond the simplex vibrating soliton pairs, multiple oscillatory motions can jointly involve in the internal dynamics, reminiscent of the shaking soliton pairs. Both quasi-periodically and chaotically evolving phase oscillations are approached in the sense of different oscillatory frequencies. In addition, the shaking soliton pair combined with sliding phase dynamics is also observed, and is interpreted as the superposition of two different internal motions. All of these results shed new light on the internal dynamics of soliton molecules with higher degrees of freedom, as well as enrich the framework toward multisoliton complexes.